Modelling and solving building physics problems using MATLAB/Simulink - N. M. M. Ramos (2005)
This article describes in detail an experimental technique and an implementation of a numerical model, in MATLAB/Simulink, used in laboratory classes of the Civil Engineering course at the Faculty of Engineering of Porto University. This work aims to motivate the students to combine laboratory experiments with computer simulation. The present work also illustrates the moisture buffer capacity of building materials. The moisture buffer capacity of building materials in transient conditions was tested in small-scale laboratory tests. Alongside, was a numerical simulation tool for hygrothermal performance analyses of buildings and building materials and both results were compared The experiment illustrates the importance of materials moisture buffer capacity in the hygrothermal behaviour of buildings; and it is important to have in mind that the majority of students do not have the opportunity to gain 'hands on' familiarity with the interplay between diffusion and sorption, nor do they have the opportunity of seeing, in practice, how it is possible to characterize porous materials in terms of their impact on indoor environment.